STUDY OF THE PROBLEM OF ALIEN FLORA IN UKRAINE AND IN THE WORLD - Киселев, Юрий; Шлапак, Владимир; Парахненко, Владислав; Черныш, Виталий (SWorldJournal, 2021)
Abstract. The article outlines the agricultural and ecological significance of the problem of alien flora. It is highlighted the main milestones of study on migrations of alien species. In particular, it is emphasized that at the first stage (before Worl